Forgrunding af ledsætninger – et psykolingvistisk forsøg - Christensen, Marie Herget; Christensen, Tanya Karoli; Jensen, Torben Juel (Ny forskning i grammatik, 2016)
It is a common phenomenon in spoken language that the main point of an utterance is found in a syntactically subordinated clause instead of in its matrix clause. This is the case in constructions where the matrix clause is semantically secondary as well as in subclauses with V>Adv word order in Danish. We argue that such subclauses are foregrounded, and that a foregrounded subclause will attract more attention than a non-foregrounded. To test this, we have conducted an experiment under the Text Change paradigm. Results show that readers pay significantly more attention to the subclause in constructions with semantically secondary matrix clauses than in constructions with semifactive matrix clauses, and, in the latter constructions, more attention to subclauses with V>Adv word order than with Adv>V word order.